Electrical stimulation mapping in the medial prefrontal cortex induced auditory hallucinations of episodic memory: A case report - Long, Qiting; Li, Wenjie; Zhang, Wei; Han, Biao; Chen, Qi; Shen, Lu; Liu, Xingzhou (Frontiers in Human Neuroscience, 2022)
It has been well documented that the auditory system in the superior temporal cortex is responsible for processing basic auditory sound features, such as sound frequency and intensity, while the prefrontal cortex is involved in higher order auditory functions, such as language processing and auditory episodic memory. The temporal auditory cortex has vast forward anatomical projections to the prefrontal auditory cortex, connecting with the lateral, medial, and orbital parts of the prefrontal cortex. The connections between auditory cortex and prefrontal cortex thus help in localizing, recognizing and comprehending external auditory inputs. Also, the medial prefrontal cortex is believed to be a core region of episodic memory retrieval, and is one of the important regions in default mode network. However, previous neural evidence with regard to the comparison between basic auditory processing and auditory episodic memory retrieval mainly comes from fMRI studies. The specific neural networks and the corresponding critical frequency bands of neuronal oscillations underlying the two auditory functions remain unclear. In the present study, we reported results of direct cortical stimulations during stereo-electro-encephalography (SEEG) recording on a patient with drug-resistant epilepsy. Electrodes covered the superior temporal gyrus, the operculum and insula cortex of bilateral hemispheres, the prefrontal cortex, parietal lobe, anterior and middle cingulate cortex, and amygdala of left hemisphere. Two types of auditory hallucinations were evoked with direct cortical stimulations, which were consistent with the habitual seizures. The noise hallucinations "I hear buzzing noises", was evoked with the stimulation of the superior temporal gyrus. The episodic memory hallucinations 'I hear a young woman saying: what is the matter with you?’, was evoked with the stimulation of the medial prefrontal cortex. The patient described that she had met this woman before and the woman said the same sentence to her. Furthermore, by analyzing the high gamma power (HGP) induced by direct electrical stimulation, two dissociable neural networks underlying the two types of auditory hallucinations were localized. Taken together, the present results confirmed the hierarchical processing of auditory information by showing the different involvements of the primary auditory cortex vs. the prefrontal cortex in the two types of auditory hallucinations.